Simian Varicella Virus DNA in Saliva and Buccal Cells After Experimental Acute Infection in Rhesus Macaques - Traina-Dorge, Vicki; Mehta, Satish; Rooney, Bridgette; Crucian, Brian; Doyle-Meyers, Lara; Das, Arpita; Coleman, Colin; Nagel, Maria; Mahalingam, Ravi (Frontiers in Microbiology, 2019)
Simian varicella virus (SVV) infection of non-human primates is the counterpart of varicella zoster virus (VZV) infection in humans. To develop non-invasive methods of assessing SVV infection, we tested for the presence of SVV DNA in saliva, as has been documented in human VZV infection, and in buccal cells to determine whether epithelial cells might provide a more reliable source of material for analysis. Five rhesus macaques intratracheally inoculated with SVV all developed varicella with viremia and macular-papular skin rash in 1-2 weeks, which resolved followed by establishment of latency. DNA extracted from longitudinal blood, saliva and buccal samples collected during acute infection and establishment of latency were analyzed by real-time qPCR. After intratracheal inoculation, viremia was observed, with peak levels of 101-102 copies of SVV DNA in 100ng of peripheral blood mononuclear cell DNA at 4 and 7 days’ post inoculation (dpi), which then decreased at 9 - 56 dpi. In saliva and buccal cells at 7 dpi, 10^1-10^4 copies and 10^1-10^5 copies of SVV DNA/ 100ng of cellular DNA, respectively, were detected in all 5 monkeys. At 9 dpi, saliva samples from only 2 of the 5 monkeys contained SVV DNA at 10^2 -10^3 copies/ 100ng of saliva DNA, while buccal cells from all 5 monkeys showed 10^0-10^3 copies of SVV DNA/100ng of buccal cell DNA. Similar to viremia, SVV DNA in saliva and buccal cells at 11-56 dpi was lower, suggesting clearance of viral shedding. SVV DNA levels were generally higher in buccal cells than in saliva. Our findings indicate that SVV shedding into the oral cavity parallels acute SVV infection and underscore the relevance of both saliva and buccal cell samples to monitor acute varicella virus infection.